Stunted child - overweight mother pairs: an emerging policy concern? - Garrett, James L.; Ruel, Marie T. (United Nations, 2003)
This paper explores the prevalence of the coexistence of a stunted child and an overweight mother in the same household (SCOWT), a somewhat paradoxical phenomenon when found in the developing world. It tests whether this phenomenon is associated with a country's level of economic development and urbanization and, by implication, the nutrition transition. It then highlights policy directions for public nutrition. Data from 42 Demographic and Health Surveys in Africa, Asia, and Latin America were used. Stunting was defined as height-for-age < −2 SD of the reference population, and maternal overweight as a body-mass index > 25 kg/m2. World Bank and United Nations figures were used for gross domestic product (GDP) per capita (an indicator of economic development) and for level of urbanization. Descriptive statistics were derived, and regression analysis was used to model the association between economic development, urbanization, and the prevalence of pairs of stunted children and overweight mothers. The prevalence of this phenomenon is generally below 10%, except in four countries, three of them in Latin America. The phenomenon is generally more prevalent in Latin America than in Africa, though not necessarily more prevalent in urban than in rural areas. The analysis finds that the phenomenon is associated with economic development, but not urbanization, and that it does differ between urban and rural areas and regions. The association with GDP per capita supports the hypothesis that SCOWT increases with economic development, up to a point. SCOWT appears to be most prevalent, as expected, in those countries in the midst of the nutrition transition. Recognizing this phenomenon is important for delineating strategies that respond to the differential needs of individuals within the household and do not just affect the household as a whole. This may become especially important with future economic development and, potentially, urbanization.